KOMPETENSI BAHASA DAN KOMPETENSI KOMUNIKATIF - Syarul Rahmanshya; Nursalim Nursalim (PENTAS : Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2020)
In everyday life, someone's language competence is very necessary. Language competence is one's mastery of the content contained in the language learned. Without language competence a person becomes irregular in language. The purpose of this study is to explain and find out about language competence or language skills and communicative competencies or one's appearance in interacting in language. Communicative competence concerns the social and cultural knowledge that speakers have to help them use and interpret linguistic forms. The problems that will be answered in this study use library research, which will answer what are the components and language competencies. Data collected from various references; both primary, secondary and supporting data. The results of the study show that there are five language competencies according to Canale and Swain namely linguistics, socio-linguistics, speech acts (speech acts), speech sets, strategies. In language competence one must master language skills, namely listening, speaking, reading and writing